High-volumetric capacitance and high-rate performance in liquid-mediated densified holey MXene film. (January 2022) - Fan, Zhimin; Yang, Yuqi; Ma, Haoxiang; Wang, Youshan; Xie, Zhimin; Liu, Yuyan
Abstract: Achieving both high-volumetric capacitance and high-rate performance in thick pseudocapacitive film materials plays a critical role in facilitating the realization of large-scale electrochemical energy storage. However, MXene (Ti3 C2 T x ), as a two-dimensional material with a high aspect ratio, is blocked by the industry problem of nanosheets self-stacking when assembled into dense films, which would induce extremely poor ionic mobility and significant attenuation of thick electrode performance. Herein, we create uniform in-plane nanopore defects in MXene nanosheets, and introduce nonvolatile liquids with different water contents, in which the interlaminar structure of holey MXene film can be accurately controlled by the capillary compression generated during evaporation. More importantly, the residual nonvolatile liquids effectively maintain the wettability of MXene surface, making it is easy to obtain compact pseudocapacitive film materials with pore structure connectivity, and allows ions to rapidly transport. The results demonstrate that the liquid-mediated densified holey MXene film can still present high-volumetric capacitance and high-rate performance at the actual mass loading level (>10 mg cm −2 ), which is of great significance for promoting the advancement of MXene materials from the theoretical elucidation to practical application. Graphical abstract: Image 1